THE INFLUENCE OF PACKAGING, BRAND AND PRODUCT QUALITY ON PURCHASING DECISIONS FOR PUCUK TEA, JEMBER REGENCY IN 2024 - Fauziah, Anisatul (JIM : Journal Of International Management, 2024)
Marketing is how to fulfill and satisfy the needs of consumers through various distribution channels, of course through the products offered. This research aims to determine the influence of brand packaging and product quality on purchasing decisions for packaged drinks from the Teh Puncak brand in Kencong sub-district, Jember Regency. Next, to find out which variables have the most influence on the decision to package the bud branded drink in Kencong sub-district, Jember Regency. The method used in this research is quantitative. The data obtained in this research was obtained from consumers who bought these products in the Kencong sub-district, Jember Regency. In determining the sample using slovin, and the results of determining the sample using slovin obtained 36 respondents. Data obtained by distributing questionnaires were analyzed using multiple linear regression analysis techniques. The test results in this research show that the brand and product quality variables do not have a significant positive impact on purchasing decisions. Then the packaging variable is able to provide a significant positive impact on purchasing decision